Two Novel Pathogenic FBN1 Variations and Their Phenotypic Relationship of Marfan Syndrome - Yalcintepe, Sinem; Demir, Selma; Atli, Emine Ikbal; Deveci, Murat; Atli, Engin; Gurkan, Hakan (Global Medical Genetics, 2020)
Marfan syndrome is an autosomal dominant disease affecting connective tissue involving the ocular, skeletal systems with a prevalence of 1/5,000 to 1/10,000 cases. Especially cardiovascular system disorders (aortic root dilatation and enlargement of the pulmonary artery) may be life-threatening. We report here the genetic analysis results of three unrelated cases clinically diagnosed as Marfan syndrome. Deoxyribonucleic acid (DNA) was isolated from EDTA (ethylenediaminetetraacetic acid)-blood samples of the patients. A next-generation sequencing panel containing 15 genes including FBN1 was used to determine the underlying pathogenic variants of Marfan syndrome. Three different variations, NM_000138.4(FBN1):c.229G > A(p.Gly77Arg), NM_000138.4(FBN1):c.165–2A > G (novel), NM_000138.4(FBN1):c.399delC (p.Cys134ValfsTer8) (novel) were determined in our three cases referred with a prediagnosis of Marfan syndrome. Our study has confirmed the utility of molecular testing in Marfan syndrome to support clinical diagnosis. With an accurate diagnosis and genetic counseling for prognosis of patients and family testing, the prenatal diagnosis will be possible.
Keywords: Marfan syndrome; novel variation; next-generation sequencing